1983
DOI: 10.1002/ana.410140513
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative sudomotor axon reflex test in normal and neuropathic subjects

Abstract: We have quantified postganglionic sweat output in human subjects resulting from axon reflex stimulation using acetylcholine electrophoresis. Dehumidified nitrogen of controlled temperature and flow rate was passed through an acrylic plastic chamber placed over a defined area of skin. Sweat droplets were evaporated; humidity change was sensed by a narrow-range humidity sensor housed in a temperature-controlled compartment and was plotted on a chart recorder. The time integral (area under the curve) was continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
276
1
14

Year Published

1989
1989
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 461 publications
(295 citation statements)
references
References 27 publications
4
276
1
14
Order By: Relevance
“…However, the size or number of active sweat glands can change after exposure to heat (Nielsen, 1998). According to Low et al (1983), the QSART with 10% ACh and 2 mA of direct current maximally stimulate sweat gland, nevertheless, they could not confirm this finding in short-term (exposure to hot summer seasons) heat acclimatization. It is possible that 10% ACh is insufficient to activate all sweat glands after acclimatization in September.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the size or number of active sweat glands can change after exposure to heat (Nielsen, 1998). According to Low et al (1983), the QSART with 10% ACh and 2 mA of direct current maximally stimulate sweat gland, nevertheless, they could not confirm this finding in short-term (exposure to hot summer seasons) heat acclimatization. It is possible that 10% ACh is insufficient to activate all sweat glands after acclimatization in September.…”
Section: Discussionmentioning
confidence: 97%
“…For example, local skin heating facilitates transmitter release at the neuroglandular junction and augments glandular responsiveness to the transmitter (Ogawa & Asayama, 1986). Lee et al (1997) and Low et al (1983) demonstrated an increase in the sweating response when the skin temperature was increased. Similarly, skin vasodilatation induced by iontophoretically applied ACh causes sweat expulsion (Sugenoya et al, 1995;Morris & Shore, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QSART is a sensitive test used to estimate the function of postganglionic peripheral sympathetic nerves, consisting of C-fibers innervating sweat glands (9). The results of QSART reflect terminal sympathetic nerve function, which maybe impaired early in diabetic peripheral neuropathy (12).…”
Section: Discussionmentioning
confidence: 99%
“…Although the Schellong test is a well-known test estimating orthostatic hypotension (OH) defined as a fall in systolic blood pressure of 30 mmHg or more when changing from lying to standing position (8), diabetic patients suffering from OHoften have severe subjective symptoms including postural weakness, faintness, visual impairment and syncope. Quantitative sudomotor axon reflex test (QSART) is a method to assess the integrity of postganglionic sympathetic sudomotorefferents whichare activated via an axon reflex by controlled iontophoretic stimulation with acetylcholine (9). It has been suggested that diabetic peripheral nerve function is disturbed in nerve length-dependent manner (10).…”
Section: Introductionmentioning
confidence: 99%